Leveraging artificial intelligence and machine learning in sport sciences: a systematic literature review of applications, outcomes, and future directions - Kumar, R.; Bogia, P.; Haq, A. U.; Singh, V.; Reddy, T. O. (Sport Sciences for Health, 2025)
Background Artificial intelligence (AI) and machine learning (ML) are transforming sports sciences by enabling precise performance analysis, injury prevention, and rehabilitation. However, inconsistencies in protocols, lack of standardization, and practical deployment challenges limit their real-world impact.